Digital instruments for precise grading of jute fibre - T, Nageshkumar; Saha, Biplab; Sardar, Gunasindhu (Indian Farming, 2024)
Grading jute fibre is essential in determining the quality and price of the final product. In India, the prevailing method of grading is the hand and eye approach, which is subjective and lacks scientific basis. However, the development of digital instruments offers a more objective and scientific assessment of jute fibre. Grading jute fibre involves considering physical parameters such as bundle strength, defects, root content, colour, and fineness. These parameters help categorize the fibre into different subdivisions and determine its overall quality. While the hand and eye method is still commonly used in procurement centers, it is time-consuming and prone to human error and bias. On the contrary, digital instruments provide a more efficient and unbiased approach to grading jute fibre. Digital instruments such as automatic bundle strength testers, fineness meters, and colour and lustre meters expedite the grading process. They offer accurate and consistent measurements, reducing the reliance on subjective judgment. This ensures that jute growers receive a fair and appropriate price for their product. To promote transparency and fairness, jute purchasing centers should embrace these digital instruments for grading jute fibre. By doing so, they can overcome the drawbacks of the traditional method and establish a more transparent and unbiased evaluation system.